2019
DOI: 10.1177/1934578x1901400114
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Talisia nervosa with Potential Utility against Metabolic Syndrome

Abstract: This study is focused on the isolation and characterization of bioactive secondary metabolites from the ethanolic extract of stems of the Panamanian plant Talisia nervosa Radlk, through a series of target-based cellular assays related to the metabolic syndrome (MetS): a combination of type 2 Diabetes Mellitus (T2DM), hypercholesterolemia, inflammation, and obesity. Bioassay guided fractionation allowed the isolation of four known compounds: (-)-catechin (1), methyl gallate (2), ethyl gallate (3), and ß-D-gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…These results suggest that AF can antagonize the undesired side effect of a full PPARγ agonist and may prevent adipogenesis and the accumulation of cytoplasmic lipid droplets during the differentiation in 3T3-L1 cells. These findings are similar to dual agonists previously reported by us and others [7,[40][41][42] and suggest that AF may have the potential for its use against obesity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest that AF can antagonize the undesired side effect of a full PPARγ agonist and may prevent adipogenesis and the accumulation of cytoplasmic lipid droplets during the differentiation in 3T3-L1 cells. These findings are similar to dual agonists previously reported by us and others [7,[40][41][42] and suggest that AF may have the potential for its use against obesity.…”
Section: Resultssupporting
confidence: 92%
“…PPARγ full agonists induce adipogenesis and enhance differentiation of preadipocytes to mature adipocytes [39]. We have previously shown the antiadipogenic effects of selected medicinal plants (T. nervosa, T. hirsuta and T. chebula) and phytochemicals (gallotannins) that possess the property of dual PPAR agonists [7,40,41]. Due to the observed dual agonistic effects of AF, we further evaluated its effect on adipogenesis and lipid accumulation in mature adipocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl gallate (88) and ethyl gallate (89) were isolated from Talisia nervosa Radlk, widespread in the tropical moist and wet forest. The evaluation of LXRα transcriptional activity showed that 88 and 89 were 3.16- and 2.62-fold activation of LXRα at a concentration of 100 µg/ml, indicating their potential utility against metabolic syndrome ( Vásqueza et al, 2019 ).…”
Section: Natural Products Targeting Liver X Receptorsmentioning
confidence: 99%
“…In vitro assays on HepG2 revealed that while (–)-catechin activated only PPARγ and not PPARα, the other three compounds activated PPARα, PPARγ and LXR, with methyl gallate being more potent than ethyl gallate on all three targets. The two gallates also reduced nitric oxide (NO) production in mouse macrophages (RAW 264.7) cells [ 71 ].…”
Section: Metabolic Syndrome and Cardiovascular Riskmentioning
confidence: 99%